Alleviating effects of pea peptide on oxidative stress injury induced by lead in PC12 cells via Keap1/Nrf2/TXNIP signaling pathway - Li, Ning; Wen, Liuding; Wang, Fangyu; Li, Tiange; Zheng, Haodan; Wang, Tianlin; Qiao, Mingwu; Huang, Xianqing; Song, Lianjun; Bukyei, Erkigul; Li, Mingming (Frontiers in Nutrition, 2022)
Background: Pb poisoning causes an oxidative stress response in the human body, a key "bridge" connecting various pathways. Oxidative stress usually implies an imbalance between pro-oxidants and antioxidants. Moreover, Nrf2, Keap1, and TXNIP proteins play an essential role in oxidative stress. Some studies showed that pea peptides could alleviate the oxidative stress response. However, the regulation and mechanism of pea peptide on oxidative stress response induced by lead in PC12 cells has not been reported. Aim: To investigate the effect and mechanism of pea peptides in alleviating oxidative damage in PC12 cells induced by Pb. Methods: In this study, cell viability was detected by CCK8(Cell Counting Kit-8). The Elisa kit determines the oxidative stress indicators, such as ROS, GSH/GSSG, MDA, SOD, CAT, GPx, and GR. The Keap1, Nrf2, and TXNIP protein expressions were tested by Western blot. Results: Pea peptides PP3, PP4, and PP6 can increase the decrease of cell viability caused by lead exposure, and the difference is statistically significant (P<0.05). PP3, PP4, and PP6 can decrease the elevation of ROS and MDA caused by lead exposure; also, they can increase the decrease of CAT, SOD, GR, GPx, and GSH/GSSG caused by lead exposure, and the difference is statistically (P<0.05). PP3, PP4, and PP6 could reduce the elevated expression of Keap1 and TXNIP caused by lead exposure; meanwhile, it could also increase the expression of Nrf2 with statistically significant differences (P<0.05). Conclusions: Pea peptides PP3, PP4, and PP6 can alleviate lead-induced oxidative stress damage in PC12 cells, and the Nrf2/Keap1/TXNIP signaling pathway plays an essential role in this process.